Adsorption and regeneration study of polyethylenimine-impregnated millimeter-sized mesoporous carbon spheres for post-combustion CO2 capture. (15th April 2016) - Wang, Mei; Yao, Liwen; Wang, Jitong; Zhang, Zixiao; Qiao, Wenming; Long, Donghui; Ling, Licheng
Graphical abstract: Schematic of the mesoporous carbon spheres based solid amine adsorbents and adsorption column for electric swing adsorption. Highlights: Mesoporous carbon spheres (MCSs) were prepared as support for CO2 capture. Effect of H2 O, O2, SO2, NO and NO2 on CO2 adsorption performance were investigated. Novel electric swing adsorption process was used to regenerate the adsorbents. Abstract: The feasibility of polyethylenimine (PEI)-impregnated millimeter-sized mesoporous carbon spheres (MCSs) for post-combustion CO2 capture is systematically studied over a wide range of adsorption and regeneration conditions. MCSs with developed mesoporous structure and good electrical conductivity are used as supports, while high-molecular-weight PEI ( Mn ∼ 10, 000) is screened to be the optimal amine due to its thermal stability. At the optimal polyethylene glycol (PEG) loading of 20 wt.%, the mass/volume-based adsorption capacity is efficiently improved by 25.7% and 109.5%, respectively. The optimized adsorbent exhibits high equilibrium adsorption capacity of 163.4 mg/g for 15% CO2 at 75 °C under dry condition, and it could be further enhanced to 187.5 mg/g at the relative humidity of 60%. The presence of O2, SO2, NO and NO2 would lead to the decreased adsorption capacity after consecutive adsorption–desorption cycles, due to the irreversible chemical reaction. Moisture could inhibit the negative effect of O2 but deteriorate the detrimental effects of SO2, NO and NO2 . Depending on the good sphericity, uniform particle size, excellent thermal/electrical conductivity and good mechanical properties of MCS, PEI-impregnated MCS adsorbents could be directly used in fixed bed system and be applicable for thermal swing adsorption (TSA), vacuum swing adsorption (VSA) and novel electric swing adsorption (ESA) processes. The adsorbents could maintain fairly stable cyclic performance during the rapid VSA process, making rapid VSA of great potential for technical–economical post-combustion CO2 capture.